1998
DOI: 10.1159/000023198
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance and Insulin Secretion in Children before and during Recombinant Growth Hormone Treatment

Abstract: This study evaluates glucose metabolism and insulin secretion in children with Ullrich-Turner syndrome (UTS), chronic renal failure (CRF) and kidney transplantation (KTx) with rh GH therapy using an intravenous glucose infusion test. Before treatment, glucose AUC was significantly increased in all patient groups when compared to normal controls. Both the early and second phases of insulin secretion were not altered. During treatment, elevated glucose AUC showed a further increase in patients with KTx but not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…There are a few small studies exploring the incidence of hyperinsulinemia in the pediatric renal transplant population. Although Filler et al (68) did not observe an increased incidence of hyperinsulinemia in their pediatric renal transplant population, two other studies revealed elevated serum insulin levels in pediatric renal transplant patients (69, 70). The independent risk factors for hyperinsulinemia in these patient populations was difficult to assess as patients were receiving growth hormone treatment, which was shown to be a risk factor.…”
Section: Hyperglycemia/insulin Resistancementioning
confidence: 94%
“…There are a few small studies exploring the incidence of hyperinsulinemia in the pediatric renal transplant population. Although Filler et al (68) did not observe an increased incidence of hyperinsulinemia in their pediatric renal transplant population, two other studies revealed elevated serum insulin levels in pediatric renal transplant patients (69, 70). The independent risk factors for hyperinsulinemia in these patient populations was difficult to assess as patients were receiving growth hormone treatment, which was shown to be a risk factor.…”
Section: Hyperglycemia/insulin Resistancementioning
confidence: 94%
“…Several studies have shown a transient elevation of glucose and insulin secretion in rhGH-treated patients with CRI or after renal transplantation [81]. There has been no report of diabetes mellitus development under rhGH, but one patient with cystinosis has been reported.…”
Section: Management Of Growth Post-transplantationmentioning
confidence: 99%
“…Up to 34% of women with TS have impaired glucose tolerance [52, 53]and up to 50% may be insulin resistant [3, 29]. Oestrogen deficiency, obesity, growth hormone therapy and oxandrolone have all been implicated, although the effect of growth hormone on insulin sensitivity wears off 6–12 months after stopping treatment without causing glucose intolerance [54, 55, 56, 57]. Insulin resistance is thought to be linked to an early metabolic defect in glucose uptake such as a muscle receptor defect [54, 58], independent of BMI, although obesity undoubtedly contributes to the problem [59].…”
Section: Clinical Manifestations Of Turner Syndrome In Adultsmentioning
confidence: 99%